STUDENTS PERCEPTION OF REFERENCES IN DESCRIPTIVE TEXT - Jamal, Deris; Bakta, Dian; Lisdawati, Ida (PROJECT (Professional Journal of English Education), 2020)
This research focuses on student perception about how to prepare to understand the use of types of references (anaphoric, cataphoric, and exophoric reference) in the Descriptive text. The objectives of this research are to find out what the types of references that many used in Descriptive text and how many types of references for all paragraph in Descriptive text. The method used in this research is a descriptive qualitative method. The researcher got the data from document analysis namely in the Descriptive text about Artikel. The result from this research are the result from the tenth paragraph of the Descriptive text that has already done to analysis, there are 6 anaphoric reference, 6 cataphoric and in this article contains an understanding of a text and a concept so students can understand about the material.